Graph Representation for the Solutions of Pythagorean Equation over the General Linear Group GL₂ (ℤ₂ ) - Mahatma, Yudi; Hadi, Ibnu; Sudarwanto, Sudarwanto; Agustine, Debby (Mathematics Study Program, Faculty of Mathematics and Natural Science, Universitas Negeri Jakarta, 2025)
In 2023, Hadi et al. found the solvability of the Fermat equation over the general linear group GL2(Zp) for p=2 and p=3. In particular, for Pythagorean equation over GL2(Z2) there are 12 solutions. In this research, we represent the set solutions as a graph and investigate the properties.